The Impact of Medical Terminology in Self-Triage Decision-Making - D’Angelo, Maria C.; Humphreys, Karin R.; Li, Timmie; Young, Meredith E. (Frontiers in Communication, 2017)
Objective: The present study examined whether medical terminology impacts self-triage decisions (deciding if and when to seek medical treatment) compared to lay terminology. Methods: Undergraduate psychology student participants read 32 hypothetical health scenarios and reported how urgently they would seek care (“In this situation, when would you seek medical attention?”, presented along with a seven-point scale, with anchors at either extreme: “Never (At the next scheduled appointment, if at all)” and “As soon as possible (Within the hour)”, reflecting the options coded as 1 and 7, respectively). Data was collected in person via a paper-based questionnaire. Scenarios included a description of symptoms, which were labelled as consistent with a particular medical disorder using either a lay disease label (e.g. “Heart Attack”) or medical terminology (e.g. “Myocardial Infarction”). The 32 health scenarios represented medical disorders that purposefully reflected a spectrum of severity, commonality, and how recently the medical terminology had entered common use. Results: For disorders for which medical terminology has been more recently established, participants reported that they would seek care more urgently when the disorder was presented using a medical label (mean(SE) = 4.08(0.23)) than when they were described using the lay disease labels (3.32(0.23), t(35) = 5.36, p < 0.001; e.g. ‘Seborrheic Dermatitis’ vs. ‘Chronic Dandruff’). However, this differential response to medical or lay disease labels was not observed for disorders for which medical terminology has been more well established (medical labels = 5.16(0.18); lay labels = 4.89(0.18), t(35) = -1.67, p = 0.104; e.g. “Heart Attack” and “Myocardial Infarction”). Conclusions: These results indicate that self-triage decision making can be readily influenced by the terminology used to identify a disorder, however, this phenomenon appears to be particularly relevant for disorders in which public opinion may still be in flux.